Mujeres y política en Río Negro (1983-2021) - Rulli, Mariana (Aperturas, 2023)
In light of legislation, political reforms, and the growing feminist mobilization in recent years, this collective publication investigates the conditions of access and political participation of women in the province of Río Negro, Argentina, in the period from the recovery of democracy in 1983 to 2021. This study focuses mainly on access to elective positions in legislative and executive powers. The works gathered offer evidence on the multiple constraints and obstacles existing for women to obtain spaces and perform political activities in Río Negro. Additionally, one of the studies contemplates the situation in the Judiciary, whose mechanisms of selection and assignment of roles and positions replicate the prevailing patterns of inequality. The novelty of the perspective proposed by this book lies in the fact that, in addition to the more usual analyses of institutional contexts, electoral and political party systems, the study incorporates the obstacles represented by the inequitable distribution of domestic and care tasks, which are mostly borne by women, with concrete negative consequences for their political activity. These difficulties appear in the voices of various female protagonists from Río Negro, who are incorporated as primary sources of the investigations. Thus, the book makes a contribution to the theoretical and empirical knowledge of women's political participation at the subnational level, and for the case of Río Negro specifically, it is the first study in this field.